Perencanaan, Perancangan, dan Pelatihan Implementasi Sistem Odoo Enterprise Resource Planning - Casyel Bersheba Limpele; Sendy Ferdian Sujadi (Journal of Smart Technology and Engineering, 2026)
Implementing the Odoo Enterprise Resource Planning (ERP) system requires strong alignment among business requirements, process design, and user readiness to ensure consistent cross-module configuration and effective adoption. This paper presents the planning, design, and training phases in a case study of an Odoo ERP system implementation. Research data were collected through observations of operational processes, interviews and discussions with stakeholders, and document reviews. The data were then modelled into To-Be business processes and mapped to system requirements. The results include the development of a Business Requirement Document (BRD) a feasibility study, an integrated process blueprint, an initial configuration design for modules supporting the flow from digital campaigns to sales and financial recording, as well as operational guidelines as the basis for user training. These deliverables help minimize the risk of cross-module configuration mismatches, clarify implementation boundaries and scope, and improve user readiness before proceeding to subsequent execution stages.